2019
DOI: 10.3991/ijim.v13i02.10023
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Aware Monitoring of Mobile Users in Sensor Networks Environment

Abstract: <p><strong>Abstract—</strong>Due to complex monitoring systems in various business domains, secrecy and privacy has become critical issue for movable resources including human being. In a mobile object monitoring systems, balancing computing resources and quality of privacy is required.  Objects can be mobile devices or users or any other moving entity. This work is presented in wireless sensor network environment. Earlier work does not consider presence of mobile objects in 3D space. We can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Everyone has an equal opportunity to express their mind regardless of their race, gender, or status in the real world [22]. Privacy and secrecy issues also have been highlighted in mobile apps/systems in education and business domains [23], [24]. In 2017 a survey on awareness of privacy has been conducted among Android users, which revealed that the level of understanding is still low [25] even though there is a raising need for privacy.…”
Section: Related Workmentioning
confidence: 99%
“…Everyone has an equal opportunity to express their mind regardless of their race, gender, or status in the real world [22]. Privacy and secrecy issues also have been highlighted in mobile apps/systems in education and business domains [23], [24]. In 2017 a survey on awareness of privacy has been conducted among Android users, which revealed that the level of understanding is still low [25] even though there is a raising need for privacy.…”
Section: Related Workmentioning
confidence: 99%
“…The SCT mobile application allows user (entrepreneur and tourist/travelers) to assess their own private destination [24], then destination manager and government agencies able to access to view assessment result in each component via mobile application and also able to compare with others creative tourism destination (see Figure 3).…”
Section: Fig 3 Sct Assessment Mobile Application User Interfacementioning
confidence: 99%